The Dates of the Four Branches of the Mabinogi - Breeze, Andrew (Studia Celtica Posnaniensia, 2018)
In a previous issue of this journal, Natasha Sumner of Harvard claimed of the Four Branches of the Mabinogi that the “exact date of composition for the text is not known”; she yet quoted Professor Catherine McKenna, also of Harvard, for the tales as certainly predating the Fall of Gwynedd in 1282. A response to Professor Sumner’s comment thus has three functions. It cites publications on the question from 1897 to 2018; reveals the scholarly disagreement therein; but concludes with evidence to put the tales in the 1120s or early 1130s.